2021
DOI: 10.1152/jn.00156.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cortical compensation for hearing loss, but not age, in neural tracking of the fundamental frequency of the voice

Abstract: Auditory processing is affected by advancing age and hearing loss, but the underlying mechanisms are still unclear. We investigated the effects of age and hearing loss on temporal processing of naturalistic stimuli in the auditory system. We employed a recently developed objective measure for neural phase-locking to the fundamental frequency of the voice (f0) which uses continuous natural speech as a stimulus, i.e. 'f0 tracking'. F0-tracking responses from 54 normal hearing and 14 hearing impaired adults of va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…While responses extracted by regressing the EEG onto the rectified broadband speech waveform were consistent with ABR wave V ( Figure 3 mid and bottom), as previously reported (Maddox and Lee, 2018 ), it remains unclear whether subcortical tracking of the F0 periodicity from the running speech signal can be extracted separately. As can be seen in Figure 3A (top left), the cross-correlation of the F0 band-passed audio with the EEG response suggests a more smooth waveform with later response peaks, as also reported in previous work (Forte et al, 2017 ; Etard et al, 2019 ; Van Canneyt et al, 2021a , b , c ). To investigate their unique predictive power, we linearly combined the broadband and F0 band-passed signals in a regression model to jointly predict the subcortical EEG response.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…While responses extracted by regressing the EEG onto the rectified broadband speech waveform were consistent with ABR wave V ( Figure 3 mid and bottom), as previously reported (Maddox and Lee, 2018 ), it remains unclear whether subcortical tracking of the F0 periodicity from the running speech signal can be extracted separately. As can be seen in Figure 3A (top left), the cross-correlation of the F0 band-passed audio with the EEG response suggests a more smooth waveform with later response peaks, as also reported in previous work (Forte et al, 2017 ; Etard et al, 2019 ; Van Canneyt et al, 2021a , b , c ). To investigate their unique predictive power, we linearly combined the broadband and F0 band-passed signals in a regression model to jointly predict the subcortical EEG response.…”
Section: Resultssupporting
confidence: 87%
“…Numerous studies have more recently used linear stimulus-response models to quantify neural tracking of running natural speech or other naturalistic stimuli in the cortex (Lalor et al, 2009 ; Ding and Simon, 2012 ; Di Liberto et al, 2020 ; Kulasingham et al, 2020 ; Kurthen et al, 2021 ). These efforts have now been extended to the subcortical auditory system (Forte et al, 2017 ; Maddox and Lee, 2018 ; Etard et al, 2019 ; Polonenko and Maddox, 2021 ; Van Canneyt et al, 2021a , b , c ), leveraging the fact that EEG responses to fast acoustic variations are dominated by subcortical sources (Bidelman, 2018 ; Saiz-Alía and Reichenbach, 2020 ). The idea of using deconvolution to model brainstem EEG responses has previously been proposed in the context of evoked responses, i.e., stimulus-triggered averages with multiple repetitions of short sounds (Elberling, 1978 ; Dau, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kulasingham et al (2020) found no age effects using MEG, which is most sensitive to cortical sources. In contrast, Van Canneyt et al (2021a) found a significant reduction in response strength with advancing age using EEG (which is more sensitive to subcortical sources than MEG and will capture both cortical and subcortical sources). This observation is in line with an age-related decrease in the phase-locking ability of the subcortical (and early cortical) auditory system.…”
Section: Neural Tracking Of the F0mentioning
confidence: 79%
“…This observation is in line with an age-related decrease in the phase-locking ability of the subcortical (and early cortical) auditory system. Van Canneyt et al (2021a) also studied the effect of hearing loss and found increased f0-tracking responses in participants with hearing impairment compared to age-matched controls. The response enhancement was due to additional cortical activity phase-locked to the f0 (with a latency of ∼40 ms), likely compensating for the reduced quality of bottom-up auditory input due to diminished peripheral auditory sensitivity.…”
Section: Neural Tracking Of the F0mentioning
confidence: 99%
“…Several potential mechanisms suggest that auditory deprivation may cause decreased socialization and affect cognitive function (Mick et al, 2014 ; Paciello et al, 2021 ). In addition, HL may cause cognitive resources to be diverted from memory function into auditory processing, which creates an excessive cognitive load on higher cortical functions (Pichora-Fuller et al, 2016 ; Van Canneyt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%